Tailoring: A case study on the application of the seventh principle of PMBOK 7 in a public institution - Rodrigues, M. C.; Domingues, L.; Oliveira, J. P. (Procedia Computer Science, 2023)
In the 7th edition of PMBOK the Tailoring process is legitimized as an essential ally in project management, since it makes several adjustments throughout the project's life cycle to provide the best possible environment to achieve the deliverables and the value added to the organization. Tailoring as a principle further highlights the unique nature of each project and the need to carry out this process continuously. Based on a unique case study, the beginning of the management functions in a sector of a public organization is discussed, as well as the adaptations made to optimize the workflow and productivity in the deliverables. From this investigation results the proposal of a framework adapted to the needs of the institution, as a starting point for the professionalization of project management.